Retroviral intasomes arising. (December 2017) - Engelman, Alan N; Cherepanov, Peter
Highlights: Retroviruses use 4, 8, or 16 integrase molecules for a common intasome core structure. A divergent linker region that connects two domains influences higher-order assembly. Intasomes seemingly represent the tetramerization of predominant solution IN species. Lentiviral structures will facilitate inhibitor design and drug resistance studies. Abstract : Retroviral DNA integration takes place in the context of the intasome nucleoprotein complex. X-ray crystal structures of functional spumaviral intasomes were previously revealed to harbor a homotetramer of integrase, and it was generally believed that integrase tetramers catalyzed the integration of other retroviruses. The elucidation of new structures from four different retroviruses over the past year has however revealed this is not the case. The number of integrase molecules required to construct the conserved intasome core structure differs between viral species. While four subunits suffice for spumaviruses, α- and β-retroviruses require eight and the lentiviruses use up to sixteen. Herein we described these alternative architectures, highlighting both evolutionary and structural constraints that result in the different integrase-DNA stoichiometries across Retroviridae.